PENGARUH PEMBERIAN MADU MURNI TERHADAP KUALITAS TIDUR LANSIA DI WILAYAH KERJA PUSKESMAS WONOMULYO - Edi Dwi Iswanto; Nur Isriani Najamuddin; Irfan Irfan; Alya Andriani (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Elderly (elderly) experience changes both physically and functionally, mentally, psychosocially, and spiritually. Complaints about difficulty sleeping at night often occur in the elderly. This is the most important thing for the elderly, so that therapy is needed that is effective and safe from side effects. Giving honey is a form of therapy by way of relaxation which is a type of non-pharmacological therapy that aims to improve sleep quality in the elderly. This study aims to determine the effect of honey on sleep quality in the elderly before and after giving pure honey in Galeso Village, Work Area of ​​the Wonomulyo Health Center, Polewali Mandar Regency. This research is a quantitative study using a quasi-experimental one group pre-post test design without a control group. The research was conducted in Galeso Village from August to September 2022. The sample in this study was 17 people. The analysis was performed using univariate and bivariate analysis. Sleep quality was measured using the PSQI questionnaire (Pittsburgh Sleep Quality Index). Based on the Wilcoxon test, the value of p = .000 (p <0.05) was obtained, which means that there is an effect of pure honey on sleep quality in the elderly. Keywords: Pure Honey, Sleep Quality, Elderly